PERAN GENDER PADA RUMAH TANGGA PETANI PADI (STUDI KASUS DI DESA PEJAMBON KECAMATAN SUMBERREJO KABUPATEN BOJONEGORO) - Siti Khusnul Muasyaroh; Keppi Sukesi; Asihing Kustanti (Agros Journal of Agriculture Science, 2024)
The research aims to determine gender roles in reproductive, productive and social activities, control and access to resources and benefits in rice farming and factors that influence gender roles in rice farming households. This study uses mixed methods, this research is a research step by combining 2 existing forms of previous research, namely qualitative and quantitative research with 30 rice farmer respondents in Pejambon Village. Gender roles in rice farming households are seen in 1) division of productive labor, 2) division of reproductive labor and 3) social society. The research results show that productive activities are dominated by men or the role of husbands in farming families to carry out work activities. While reproductive activities are dominated by women, gender equality in control and access to resources and benefits proves the dominant role of men. Several factors that influence gender roles include: level of education, economic conditions and culture.